2017
DOI: 10.1016/j.avb.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the shadows of meaning: Meaning-making for perpetrators of homicide

Abstract: Human beings are thought to have unique capacities to interpret and make meaning after major life events. However this process may be complicated and difficult after events that involve anger and aggression and when dangerousness and destructiveness come to the fore. Meaning making may be especially challenging when such an event is incomprehensible to the victim's family and society, due to the perpetrator's irreversible actions and the painful awareness that a human life has been lost. Meaning-making for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 139 publications
(152 reference statements)
2
10
0
1
Order By: Relevance
“…The redemption narrative illustrates how some of the participants approach and understand themselves and the therapeutic process after the femicide; it aligns with literature which found a similar structural narrative in the sense-making process of homicide perpetrators (Ferrito et al, 2012(Ferrito et al, , 2017. The redemption narrative was found among men (n = 4) who described intimate partner violence in their relationship(s), who rationalized this violence, and who viewed the intimate femicide from the perspective of an internal locus of explanation focused on themselves.…”
Section: Redemption Archetypesupporting
confidence: 77%
See 2 more Smart Citations
“…The redemption narrative illustrates how some of the participants approach and understand themselves and the therapeutic process after the femicide; it aligns with literature which found a similar structural narrative in the sense-making process of homicide perpetrators (Ferrito et al, 2012(Ferrito et al, , 2017. The redemption narrative was found among men (n = 4) who described intimate partner violence in their relationship(s), who rationalized this violence, and who viewed the intimate femicide from the perspective of an internal locus of explanation focused on themselves.…”
Section: Redemption Archetypesupporting
confidence: 77%
“…Different disciplines and theoretical schools-including life-course criminology (Farrington, 2003), cultural criminology (Ferrell, 1997), and the sociology and anthropology of violence (Collins, 2009;Riches, 1986) have addressed how perpetrators narrate their lives and how they signify violence. Biographical studies of homicide perpetrators have shown the profound impact of harsh experiences, especially during childhood, in future violence perpetration (Ferrito et al, 2017;Viscardi, 2006). The low/high threshold-tolerance of violence has also been a common focus of attention to analyze how violent acts are minimized and normalized both in daily routines (Heilman & Barker, 2018;Launius & Hassel, 2015) and extraordinary circumstances (Roy, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A story (which is one of the principal types of narrative) has a structure or content that is susceptible to analysis, as amply shown in the humanities and social sciences (LABOV, 1972;LABOV and WALETZKY, 1997;MISHLER, 1995;RIESSMAN, 2005), including criminology (ALTHOFF et al, 2020;PRESSER and SANDBERG, 2015b). In particular, "Narrative Criminology" (PRESSER, 2009) has sought to use narrative analysis to study offenders' subjective interpretations of their crimes and the ways in which their meanings are created and communicated through stories (FERRITO et al, 2017;PRESSER and SANDBERG, 2015b). Narrative criminologists are interested in the stories that offenders tell about their crimes, because those stories reveal the ways in which offenders make sense of their experiences and construct their identities and sense of self (PRESSER, 2004;SANDBERG et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Of direct relevance is, Ferrito, Needs and Adshead's (2017) summary of the literature in relation to meaning-making processes and what meanings are made for and by the offender in the aftermath of homicide.…”
Section: Introductionmentioning
confidence: 99%